Heart beat sensor circuit for anti - stress chair - Farah Athirah Jamal Mohamad (School of Microelectronics, University Malaysia Perlis, 2015)
Heart beat sensor circuit for Anti-Stress Chair is development of microcontroller based for detecting heartbeat rate and LCD to display an output. This project is developing for the patient who needs periodically monitoring, athlete and stress person. Heart beat sensor for Anti Stress Chair is the improvement from the fixed heartbeat monitoring machine at the hospital which this project are developing in small size, portable and affordable for all range of ages. The circuit consists of TCRT 1000 which consist of phototransistor and infrared emitter in one small component acts as a sensor. LM324 is a quad low bandwidth Op-Amp which can control four different operations at the same time. It act as amplifier which process of squaring and amplification occur here. Microcontroller 8051 with IC P89V51RB2 is the heart of the circuit as it controls all the activities of the project. All data will store here before it sends to LCD to display as an output.